Barreira geotêxtil: retenção e contenção de sedimentos carreados pelo escoamento superficial em mineradoras - Lima Júnior, José Carlos de; Bernardes, George de Paula [UNESP] (My University, 2014)
Miners activity results in a significant volume of waste, which is normally deposited in piles. This paper analyzes the behavior of geotextile barrier to control fine soil runoff in a quarry. Two types of geotextile was investigated in order to evaluate the retention efficiency and deterioration after several use.